Cardiac Vagal Control and Depressive Symptoms: The Moderating Role of Sleep Quality. Issue 6 (2nd November 2017) - Werner, Gabriela G.; Ford, Brett Q.; Mauss, Iris B.; Schabus, Manuel; Blechert, Jens; Wilhelm, Frank H.
Abstract : Lower cardiac vagal control (CVC) has been linked to greater depression. However, this link has not been consistently demonstrated, suggesting the presence of key moderators. Sleep plausibly is one such factor. Therefore, we investigated whether sleep quality moderates the link between CVC (quantified by high-frequency heart rate variability, HF-HRV) and depressive symptoms (assessed using established questionnaires) in 29 healthy women. Results revealed a significant interaction between HF-HRV and sleep quality in predicting depressive symptoms: participants with lower HF-HRV reported elevated depressive symptoms only when sleep quality was also low. In contrast, HF-HRV was not associated with depressive symptoms when sleep quality was high, suggesting a protective function of high sleep quality in the context of lower CVC.